The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4097/kjae.2010.59.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Transient cortical blindness after heart surgery in a child patient -A case report-

Abstract: Visual loss occurring after pediatric cardiac surgery employing cardiopulmonary bypass (CPB) is relatively rare but the risk is substantial. Compromised cerebral perfusion due to a CPB related micro-embolization and inflammatory vascular changes as well as reduced oxygen carrying capacity in hemodilution and hypothermia during CPB might be major contributing factors to the development of postoperative visual loss after cardiac surgery with CPB. A case of immediate but transient postoperative visual loss was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[7] Recovery has been reported to begin after 28 days, [8] but in the present case even four months postoperatively, restoration of vision was only up to the perception of light. Acid base balance must be maintained preferably by the pH-stat method and whole blood or packed cells should be used for pump priming.…”
mentioning
confidence: 63%
“…[7] Recovery has been reported to begin after 28 days, [8] but in the present case even four months postoperatively, restoration of vision was only up to the perception of light. Acid base balance must be maintained preferably by the pH-stat method and whole blood or packed cells should be used for pump priming.…”
mentioning
confidence: 63%
“…Following CB the loss of vision may be permanent or transient. [ 12 13 14 15 ] The recovery of vision if happens may take variable period depending on various factors. Best prognosis has been observed in patients under the age of 40 years, in those without a history of hypertension or diabetes mellitus, and in those without associated cognitive, language, or memory impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al analyzed the data for more than 5.6 million patients who underwent various nonophthalmic surgeries between 1996 and 2005, and found that cardiac surgery had the highest rates of perioperative visual loss among nonophthalmic surgeries, specifi cally 8.64 cases per 10,000 patients [Shen 2009]. These cases are usually caused by emboli, hypotension, acute anemia, hypoxia, intraparenchymal hemorrhage, or a combination of these factors [Slavin 1987;Shahian 1989;Moster 1998;Chen 2000;Sha'aban 2000;Loubani 2001;Suzuki 2001;Bagheri 2008;Thurtell 2008;Shin 2010]. In the case of our patient, these causes have been carefully considered and ruled out by the workup of the neurology, ophthalmology, and neuro-ophthalmology services.…”
Section: Discussionmentioning
confidence: 99%